Readjustment of circadian clocks by exercise intervention is a potential therapeutic target for sleep disorders: a narrative review - Lee, Kwangjun; Hong, Kwang-Seok; Park, Jonghoon; Park, Wonil (Physical Activity and Nutrition, 2024)
[Purpose] Circadian clocks are evolved endogenous biological systems that communicate with environmental cues to optimize physiological processes, such as the sleep-wake cycle, which is nearly related to quality of life. Sleep disorders can be treated using pharmacological strategies targeting melatonin, orexin, or core clock genes. Exercise has been widely explored as a behavioral treatment because it challenges homeostasis in the human body and affects the regulation of core clock genes. Exercise intervention at the appropriate time of the day can induce a phase shift in internal clocks. Although exercise is a strong external time cue for resetting the circadian clock, exercise therapy for sleep disorders remains poorly understood.[Methods] This review focused on exercise as a potential treatment for sleep disorders by tuning the internal circadian clock. We used scientific paper depositories, including Google Scholar, PubMed, and the Cochrane Library, to identify previous studies that investigated the effects of exercise on circadian clocks and sleep disorders.[Results] The exercise-induced adjustment of the circadian clock phase depended on exercise timing and individual chronotypes. Adjustment of circadian clocks through scheduled morning exercises can be appropriately prescribed for individuals with delayed sleep phase disorders. Individuals with advanced sleep phase disorders can synchronize their internal clocks with their living environment by performing evening exercises. Exercise-induced physiological responses are affected by age, sex, and current fitness conditions.[Conclusion] Personalized approaches are necessary when implementing exercise interventions for sleep disorders.